Status of captive wild animals in safari park, Malakand, Dir (L), Khyber Pakhtunkhwa, Pakistan - ud Din Yousufzai , Sultan; Ali, Ifat; Rabia, Bibi; Usman Ali Hashmi, Muhammad; Safi, Amtyaz (SPC Journal of Environmental Sciences, 2024)
Captive breeding is the process of raising wild animals under controlled conditions in zoos and wildlife sanctuaries. In this study, the conditions of animals kept in wild park located in Dir lower District of Malakand were analyzed. The aim of this study is to evaluate the status of the vertebrate fauna and to identify important problems regarding its captive breeding, conservation and management. This study suggests that mitigation measures can be taken as planning for future conservation and development.This study aims to investigate the status of different wild animals from November 2021 to September 2022 and understand the basics of conservation and management of Malakand Wildlife Park. The park covers 240 acres and is fenced. Animals are treated with good care and environment. Some of the species of animals protected in the park include leopard, urial, gray goral, monkey and pheasant which are included in the IUCN list of threatened or endangered species. The park also has a well-developed Kalij breeding Centre. This protected park also aims to promote tourism and raise the awareness of local communities to be directly involved in the management and protection of wildlife and the environment.